Mexico eaudiobook Stories. - Barkan, Josh (HighBridge Audio, 2017)
The characters in these stories are everyday citizens-a chef, architect, nurse, high school teacher, painter, beauty queen, classical bass player, plastic surgeon, businessman, mime-simply trying to lead their lives and steer clear of violence. Yet inevitably, violence has a way of intruding on their lives. A surgeon finds himself forced into performing a risky procedure on a narco killer. A teacher struggles to protect love-struck students whose forbidden romance has put them in mortal danger. A painter's freewheeling ways land him in the back of a kidnapper's car. Again and again, the lines between "ordinary life" and cartel violence are shown to be paper thin, with tragic results. Though the lives of Mexico's characters are effected by the corrupt and dangerous subculture of their country, these are much more than simple "crime stories". They are complicated and deeply moving tales that tap into universal and enduringly powerful themes: love and loss, religion, family relationships, government abuse, sexual identity, professional ambition, cancer; they introduce us to characters that feel fully realized in their humanity.